Research of the angular distribution of errors at different transmission speeds in the decameter range - Bulaga, V.A. (Radiotekhnika, 2024)
The paper states that the main factors that affect the reduction of bandwidth and reliability of communication channels in the decameter range are multiradiation and the level of interference from transmitters operating at close frequencies. It is known that one of the methods of combating such negative phenomena is the use of phased antenna arrays in communication systems. The paper evaluates the efficiency of the phased antenna system according to the information criterion "error coefficients – elevation angle". The angular distribution of errors at different transmission speeds in the short-wave range when using phased antenna arrays was studied according to the information criterion "error coefficients – angle of position". The results obtained in the work allow us to draw the following conclusions: the possibility of using error detection devices when testing the reliability of communication channels is fully confirmed communication of the decameter range; the use of controlled phased antenna arrays on the receiving side allows to solve a complex of trajectory tasks, and also allows to evaluate the effectiveness of communication systems that use beam distribution at the reception.